The Law of Ancient Athens - Phillips, David D., 1971- (Book collections on Project MUSE., 2013)
"The Law of Ancient Athens contains the principal literary and epigraphical sources, in English, for Athenian law in the Archaic and Classical periods, from the first known historical trial (late seventh century) to the fall of the democracy in 322 BCE. This accessible and important volume is designed for teachers, students, and general readers interested in the ancient Greek world, the history of law, and the history of democracy, an Athenian invention during this period. Offering a comprehensive treatment of Athenian law, it assumes no prior knowledge of the subject and is organized in user-friendly fashion, progressing from the person to the family to property and obligations to the gods and to the state. David D. Phillips has translated all sources into English, and he has added significant introductory and explanatory material. Topics covered in the book include homicide and wounding; theft; marriage, children, and inheritance; citizenship; contracts and commerce; impiety; treason and other offenses against the state; and sexual offenses including rape and prostitution. The volumes unique feature is its presentation of the actual primary sources for Athenian laws, with many key or disputed terms rendered in transliterated Greek. The translated sources, together with the topical introductions, notes, and references, will facilitate both research in the field and the teaching of increasingly popular courses on Athenian law and law in the ancient world"--Unedited summary from book cover